2018
DOI: 10.1101/gad.314815.118
|View full text |Cite
|
Sign up to set email alerts
|

POU2F3 is a master regulator of a tuft cell-like variant of small cell lung cancer

Abstract: Small cell lung cancer (SCLC) is widely considered to be a tumor of pulmonary neuroendocrine cells; however, a variant form of this disease has been described that lacks neuroendocrine features. Here, we applied domain-focused CRISPR screening to human cancer cell lines to identify the transcription factor (TF) POU2F3 (POU class 2 homeobox 3; also known as SKN-1a/OCT-11) as a powerful dependency in a subset of SCLC lines. An analysis of human SCLC specimens revealed that POU2F3 is expressed exclusively in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
395
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(423 citation statements)
references
References 39 publications
26
395
2
Order By: Relevance
“…Poirier et al, using a similar clustering approach to ours, identified highly methylated SCLC subtypes (M1 364 and M2) [29], and the correspondence of these subtypes with the ones described here is intriguing and remains to be defined. 365 Finally, Huang et al recently reported an SCLC subtype defined by expression of POU2F3 [12]. In our data, POU2F3 was 366 highly expressed in only four cell lines, and was placed POU2F3 into a small (328 genes, green-yellow) module, and therefore 367 represented only a small signal in our data.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Poirier et al, using a similar clustering approach to ours, identified highly methylated SCLC subtypes (M1 364 and M2) [29], and the correspondence of these subtypes with the ones described here is intriguing and remains to be defined. 365 Finally, Huang et al recently reported an SCLC subtype defined by expression of POU2F3 [12]. In our data, POU2F3 was 366 highly expressed in only four cell lines, and was placed POU2F3 into a small (328 genes, green-yellow) module, and therefore 367 represented only a small signal in our data.…”
mentioning
confidence: 51%
“…In both human and mouse tumors, most cells appear to belong to the NE subtype, 55 corresponding to a pulmonary neuroendocrine cell (PNEC) of origin [9], with high expression of neuroendocrine genes such as 56 ASCL1. However, several groups have found evidence for non-NE variants within SCLC tumors [10][11][12], as well as an NE 57 variant driven by MYC overexpression and NEUROD1 overexpression, instead of ASCL1 [13-15]. We previously described 58 SCLC cell lines with hybrid expression of both NE and non-NE markers [16], and proposed they could serve as a resistant 59 niche since drug perturbations shifted most cell lines towards hybrid phenotype(s).…”
mentioning
confidence: 99%
“…We have previously demonstrated that prior to the application of drug, there is a rare subpopulation of cells (pre-resistant cells) that express high levels of a number of markers, and that these "primed" cells are far more likely to become resistant than other cells 14 . In order to identify modulators of the fluctuations that lead to the formation of this subpopulation of primed cells, we designed a large scale loss-of-function pooled CRISPR genetic screen (which we dubbed the "priming screen") comprised of ~13,000 single guide RNAs (sgRNAs) targeting functionally relevant domains of ~2,000 proteins, with roughly six distinct single guide RNAs per domain (1402 transcription factor targets, 481 kinase targets, 176 epigenetic targets; each single guide RNA targets an important functional domain, see Supplemental Tables 1-3) [27][28][29] .…”
Section: Crispr/cas9 Genetic Screens Identify Factors That Affect Primentioning
confidence: 99%
“…Approximately 6 independent single guide RNAs were designed against individual DNA binding domains (Supplementary tables 1-3). [27][28][29] The design principle of single guide RNA was based on previous reports and the single guide RNAs with the predicted high off-target effect were excluded (Hsu et al 2013) . For the initial pooled CRISPR screens, all of the single guide RNAs oligos including positive and negative control single guide RNAs were synthesized in a pooled format (Twist Bioscience) and then amplified by PCR.…”
Section: Construction Of Domain-focused Single Guide Rna Pooled Librarymentioning
confidence: 99%
“…It is also possible that some of SCLC lines may have a different cell of origin. For example, it was recently proposed that some of neuroendocrine marker negative SCLC may have originated from tuft cells (30). POU2F3, TRPM5, GNG13 are considered tuft cells markers, interestingly the NCI-H211 SCLC line, which is a typical neuroendocrine marker negative RB1 WT line, has comparatively high mRNA expression of these 3 markers.…”
Section: Oncogenic Alterations In Wt Rb1 Sclcmentioning
confidence: 99%